Risk of early onset pneumonia in neonates with abnormal gastric aspirate - IB. Mahendra; I Wayan Retayasa; I Made Kardana (Indonesian Pediatric Society Publishing House, 2008)
Background Early onset neonatal pneumonia is the risk factor for neonatal sepsis that increases risk for neonatal deaths. Recognition, prevention, and treatment of this problem is major factors in the managemant of high risk neonates. Analysis of gastric aspirate, collected soon after birth is a useful screening test for predicting pneumonia. Objective To evaluate the risk of early onset of neonatal pneumonia in neonates with abnormal gastric aspirate. Methods A case control study was done on infants with early onset neonatal pneumonia born in Sanglah Hospital during the period of July 2004 until November 2005. The control group consisted of high risk infants without early onset pneumonia. Multiple logistic regressions was performed to determine the confounding effects of multiple variables that were considered as risk factors for early-onset neonatal pneumonia. Results Forty-five infants with early onset neonatal pneumonia were recruited. Multivariate analysis showed that abnormal gastric aspirate and low APGAR score were significant factors associated with early-onset of neonatal pneumonia with OR 4.05 (95%CI 1.26;13,02), P=0.019, and OR 6.95 (95%CI 2.45;19.77), P<0.0001, respectively. Conclusion Abnormal gastric aspirate and low APGAR score are risk factors for early onset neonatal pneumonia in high risk infants.